2016
DOI: 10.1021/acsnano.6b06828
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Hyperporous Silicon Flake Anodes for High Initial Coulombic Efficiency and Cycle Stability

Abstract: Three-dimensional (3D) hyperporous silicon flakes (HPSFs) are prepared via the chemical reduction of natural clay minerals bearing metal oxides. Natural clays generally have 2D flake-like structures with broad size distributions in the lateral dimension and varied thicknesses depending on the first processing condition from nature. They have repeating layers of silicate and metal oxides in various ratios. When the clay mineral is subjected to a reduction reaction, metal oxide layers can perform a negative cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…However, its relatively low theoretical capacity of 372 mA h g −1 offers room to develop novel high energy density negative electrodes. [49] To better accommodate the volumetric changes of the material and enable the commercial application of Si-based anodes, research is being conducted on the production of nanostructured [51] and core-shell Si electrodes. [46][47][48] • Another strategy to improve the energy density and to reduce the costs of Li-ion batteries is to develop silicon or metallic lithium anodes.…”
Section: Batteriesmentioning
confidence: 99%
“…However, its relatively low theoretical capacity of 372 mA h g −1 offers room to develop novel high energy density negative electrodes. [49] To better accommodate the volumetric changes of the material and enable the commercial application of Si-based anodes, research is being conducted on the production of nanostructured [51] and core-shell Si electrodes. [46][47][48] • Another strategy to improve the energy density and to reduce the costs of Li-ion batteries is to develop silicon or metallic lithium anodes.…”
Section: Batteriesmentioning
confidence: 99%
“…In terms of controlling the reaction kinetics, salt crystals (e. g., sodium chloride, potassium chloride or these of mixture) – which have higher melting points than metal reductants – play a crucial role as heat scavengers ,. After proper acid leaching, the Si produced in this manner has a mesoporous structure with a broad distribution of pore sizes that can fall into the range of mesopores or sometimes even macropores .…”
Section: Preparation Of Nanostructured Simentioning
confidence: 99%
“…After proper acid leaching, the Si produced in this manner has a mesoporous structure with a broad distribution of pore sizes that can fall into the range of mesopores or sometimes even macropores . The developed pores provide a high surface‐area‐to‐volume ratio that can speed up lithiation/delithiation kinetics and accommodate volume changes that arise from the formation of lithium silicide, thereby reducing the surface stress ,…”
Section: Preparation Of Nanostructured Simentioning
confidence: 99%
“…Magnesiothermic reduction method is a widely used approach to synthesize silicon based anode materials [68][69][70][71]. For instance, Xie et al reported a porous silicon nanoparticle formation through magnesiothermic reduction synthesis by using the monodisperse silica sphere as stating material [72].…”
Section: Silicon Nanoparticle/carbonmentioning
confidence: 99%